Achieving a 'top-down' change agenda by driving and supporting a collaborative 'bottom-up' process: case study of a large-scale enhanced recovery programme. Issue 2 (26th October 2017) - Ogunlayi, Fatai; Britton, Philip
Abstract : There is increasing recognition that organisations need to look beyond their boundaries for new innovations. However, the introduction and implementation of best practice that has been developed externally may need different processes of implementation if a successful change process is going to be achieved. Using an enhanced recovery programme as an example, we report a case study that combines the best of a top-down approach with the principles of bottom-up collaborative working to successfully embed a large-scale quality improvement programme that was commissioned to improve the adoption of enhanced recovery in elective surgery. We describe a large-scale change programme that was established, coordinated and driven from within a central 'top' organisation but delivered and owned locally by individual organisations working collaboratively across southeast region of England. We discuss why we believe our methodology of implementing this programme was successful, the important triggers for success and the lessons we learned from the programme.